SphK2/S1P Promotes Metastasis of Triple-Negative Breast Cancer Through the PAK1/LIMK1/Cofilin1 Signaling Pathway - Shi, Weiwei; Ma, Ding; Cao, Yin; Hu, Lili; Liu, Shuwen; Yan, Dongliang; Zhang, Shan; Zhang, Guang; Wang, Zhongxia; Wu, Junhua; Jiang, Chunping (Frontiers in Molecular Biosciences, 2021)
Background: Triple-negative breast cancer (TNBC) features a poor prognosis, which is partially attributed to its high metastatic rate. However, there is no effective target for systemic TNBC therapy due to the absence of estrogen, progesterone, and human epidermal growth factor 2 receptors (ER, PR, HER-2, respectively) in the cancer. In the present study, we evaluated the role of sphingosine kinase 2 (SphK2) and its catalyst sphingosine-1-phosphate (S1P) in TNBC metastasis and the effect of the SphK2-specific inhibitor ABC294640 on TNBC metastasis. Methods: The function of SphK2 and S1P in TNBC cell metastasis was evaluated using transwell migration and wound-healing assays. The molecular mechanism of SphK2/S1P mediating TNBC metastasis was investigated using Western blot, histological examination and immunohistochemistry assays. The antitumor activity of ABC294640 was examined in an in vivo TNBC lung metastatic model. Results: SphK2 promoted TNBC cell migration through the generation of S1P. Targeting SphK2 with ABC294640 inhibited TNBC lung metastasis in vivo. p21-activated kinase 1 (PAK1), p-Lin-11/Isl-1/Mec-3 kinase 1 (LIMK1) and Cofilin1 were the downstream signaling molecules of SphK2/S1P. Inhibition of PAK1 suppressed SphK2/S1P-induced TNBC cell migration. Conclusion: SphK2/S1P promotes TNBC metastasis through the activation of the PAK1/LIMK1/Cofilin1 signaling pathway. ABC294640 inhibits TNBC metastasis in vivo and could be developed as a novel agent for the clinical treatment of TNBC.